ORGANIZATION AND DESIGN OF RESIDENTIAL BUILDINGS IN CONSTRUCTION - Solijonov Javoxirmirzo Obidjon o‘g‘li; Normirzayev Avazxon Akram o‘g‘li; Kamilova Omina Zoxidjon qizi (ANTIS PUBLISHER, 2024)
Construction design for materials own into takes one series standard to constructions based on citizenship buildings construction in engineering used elements and systems . They are with one in line in the textbook experimental designs shown leader project institutions and persons by work issued foreign companies